Central sympathetic nerve activation in subarachnoid hemorrhage. Issue 1 (9th October 2021) - Hasegawa, Yu; Uchikawa, Hiroki; Kajiwara, Sosho; Morioka, Motohiro
Abstract: Subarachnoid hemorrhage (SAH) is a life‐threatening condition, and although its two main complications—cerebral vasospasm (CVS)/delayed cerebral ischemia (DCI) and early brain injury (EBI)—have been widely studied, prognosis has not improved over time. The sympathetic nerve (SN) system is important for the regulation of cardiovascular function and is closely associated with cerebral vessels and the regulation of cerebral blood flow and cerebrovascular function; thus, excessive SN activation leads to a rapid breakdown of homeostasis in the brain. In the hyperacute phase, patients with SAH can experience possibly lethal conditions that are thought to be associated with SN activation (catecholamine surge)‐related arrhythmia, neurogenic pulmonary edema, and irreversible injury to the hypothalamus and brainstem. Although the role of the SN system in SAH has long been investigated and considerable evidence has been collected, the exact pathophysiology remains undetermined, mainly because the relationships between the SN system and SAH are complicated, and many SN‐modulating factors are involved. Thus, research concerning these relationships needs to explore novel findings that correlate with the relevant concepts based on past reliable evidence. Here, we explore the role of the central SN (CSN) system in SAH pathophysiology and provide a comprehensive review of the functional CSN network; brain injury in hyperacute phase involving the CSN system; pathophysiological overlap between the CSN system and the two major SAH complications, CVS/DCI and EBI; CSN‐modulating factors; and SAH‐related extracerebral organ injury. Further studies are warranted to determine the specific roles of the CSN system in the brain injuries associated with SAH. Abstract : Central sympathetic nerve (CSN) activation in subarachnoid hemorrhage (SAH) characterizes hypothalamic injury in addition to intracranial pressure (ICP) elevation. It leads to the up‐regulation of catecholamine (catecholamine surge) and CSN‐modulating factors including renin–angiotensin system, neuropeptide Y, vasopressin, brain‐derived neurotrophic factor (BDNF), and perivascular macrophage; and SAH‐related extracerebral organ injury. We herein propose that CSN activation in SAH is involved in independent events of the same rank as early brain injury and cerebral vasospasm (CVS)/delayed cerebral ischemia (DCI), although all of them share some of the same pathogenic factors.